Multiyear hygrothermal performance simulation of historic building envelopes. Issue 1 (October 2021) - Libralato, M; De Angelis, A; D'Agaro, P; Cortella, G; Saro, O
Abstract: The objective of this work is to quantify the effects of the short-term climate change with a multiyear (MY) approach on the results of the heat and moisture transfer simulations of an historic building located in Udine (Italy) and to evaluate if a single year simulation could be representative of the results obtained with the MY. The hygrothermal performance and the moisture related risk are evaluated for a brick wall with and without insulation, with a MY of 25 years and with three single years selected form the MY. The software DELPHIN is used for the simulations and the damage indicators are calculated using simplified methods (number of days with unfavourable conditions). Depending on the damage considered, the years have different effects on the studied wall. The simulations that use the MY weather file allow to obtain more accurate results than using one-year simulations, but the effort and time required for the interpretation of the simulation results could be not acceptable. It is then shown that the choice of a representative weather file is crucial to the results of the risk analysis and that considering more than one weather file is necessary to obtain representative results for different damages mechanisms.